Emotion-regulation skills as a treatment target in psychotherapy - Berking, Matthias; Wupperman, Peggilee; Reichardt, Alexander; Pejic, Tanja; Dippel, Alexandra; Znoj, Hansjörg (Behaviour Research and Therapy, 2008)
Background: Deficits in emotion-regulation skills have been shown to be integral to the development and maintenance of a wide range of mental disorders. Aim: To evaluate the importance of these skills as a treatment target in psychotherapeutic interventions. Method: Nine specific emotion-regulation skills were assessed in a sample of 289 inpatients before and after cognitive-behavioural treatment. Self-reports of success in pretreatment skills application were first compared to those of 246 non-clinical controls. Pretreatment skills application and change in skills application during therapy were then related to a variety of outcome measures. Finally, the effects of integrating a brief training of general emotion-regulation skills into the CBT-based treatment were evaluated in a controlled trial. Results: Uni- and multivariate analyses identified the skills of acceptance, tolerance, and active modification of negative emotions as particularly important for current mental health and treatment outcome. Replacing parts of the standard CBT treatment with the emotion-regulation training enhanced the effects of the CBT treatment on skills application and on other measures of mental health. Conclusion: Incorporating interventions that directly target general emotion-regulation skills may improve the effectiveness of psychotherapeutic interventions. © 2008 Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Emotion regulation; Emotion-regulation skills; Mental health; Psychotherapy; Skills training